2020
DOI: 10.1038/s41467-020-14968-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrated proteogenomic deep sequencing and analytics accurately identify non-canonical peptides in tumor immunopeptidomes

Abstract: Efforts to precisely identify tumor human leukocyte antigen (HLA) bound peptides capable of mediating T cell-based tumor rejection still face important challenges. Recent studies suggest that non-canonical tumor-specific HLA peptides derived from annotated non-coding regions could elicit anti-tumor immune responses. However, sensitive and accurate mass spectrometry (MS)-based proteogenomics approaches are required to robustly identify these noncanonical peptides. We present an MS-based analytical approach that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
230
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(263 citation statements)
references
References 96 publications
12
230
0
Order By: Relevance
“…It has been proposed that up to 10% of the MHCI bound peptides can originate from non-coding genomic regions, untranslated regions and exonic out-of-frame translation. Additional sources of cryptic antigens can be long non-coding RNAs, altered mRNA splicing events, small nucleolar RNAs, and proteins encoded in ribosomal DNA [ 197 ]. If one takes into account that 99% of tumor-specific mutations are located in non-coding regions, these cryptic MHCI antigens can be a very rich source of tumor-specific antigens [ 197 , 198 ].…”
Section: Tumor Antigens and Tumor-associated Antigenic Peptidesmentioning
confidence: 99%
“…It has been proposed that up to 10% of the MHCI bound peptides can originate from non-coding genomic regions, untranslated regions and exonic out-of-frame translation. Additional sources of cryptic antigens can be long non-coding RNAs, altered mRNA splicing events, small nucleolar RNAs, and proteins encoded in ribosomal DNA [ 197 ]. If one takes into account that 99% of tumor-specific mutations are located in non-coding regions, these cryptic MHCI antigens can be a very rich source of tumor-specific antigens [ 197 , 198 ].…”
Section: Tumor Antigens and Tumor-associated Antigenic Peptidesmentioning
confidence: 99%
“…Since cryptic MAPs cannot be identified using canonical protein databases, Laumont et al have recently developed a proteogenomic-based approach to identify both of canonical and cryptic MAPs specific to tumor cells (e.g., mutated and aberrantly expressed TSA) (93). In parallel of this, two proof-ofprinciple studies established that MAPs can also be identified using reference databases built from ribosome profiling (Riboseq) (137,138). Ribo-Seq is based on the sequencing of mRNA fragments protected for ribonuclease digestion by their location within the ribosome decoding site.…”
Section: Tumor-specific Antigen Derived From Aberrant Translationmentioning
confidence: 99%
“…In the second approach, normal adjacent tissue (not tumor-infiltrated) is used as a negative control [ 50 ]. Once again, the absence of a MAP in the normal adjacent tissue does not guarantee that it is not present in other cell types in the organism.…”
Section: Strategies For Mass Spectrometry-based Identification Of mentioning
confidence: 99%